Acceleration Of The Learning Process By Implementing E-Learning To Improve The Academic Quality Of The Computer Science Program, Faculty of Science and Technology, State Islamic University of North Sumatra, Medan - Armansyah; Harahap, Lailan Sofinah; Sriani (Cattleya Darmaya Fortuna, 2024)
In today's digital era, a satisfaction-service is needed in the field of education. The satisfaction service is in the form of the quality-of-a-Study Program-which-is-very much determined by-the-quality of the service provided, where-quality-service can be identified through-student-satisfaction when carrying out-learning. One of the-service-breakthroughs-by utilizing information technology that can be applied by the Computer Science-study-program, Faculty of Science-and-Technology, State-Islamic University-of North-Sumatra-Medan today-is by applying-technology-based learning with-the E-Learning program.